INDOOR AIR QUALITY IN SCHOOLS / DAYCARE CENTERS (Tufts Archival Research Center, 2007)
Missing Attachments; Report on the air quality in schools. Blames poor air quality in schools on inadequate ventilation systems and points out that even places where smoking is banned have air quality problems.